A Model for Individual Height Estimation from Forearm Length in Natives of Kerman, Iran - Seyed Hassan Eftekhar Vaghefi; Fatemeh Sheikhbahaei; Tahmineh Mokhtari; Frouzan Khademi; Hassan Bahari; Rostam Ghorbani (Negah Institute for Scientific Communication, 2014)
Introduction: Height is an important biological human characteristic in anthropological studies and forensic medicine. In this way, forearm length (FAL) can be a useful factor for the height prediction in different population. The goal of this study was to find the relation between FAL and height in natives of Kerman. Methods: In a cross-sectional study, 150 cases including 75 males and 75 females (aged 18 to 22 years) of Kermanian population were randomly selected. In all cases height and left forearm were measured in standard positions. For finding the relation between FAL and the height, linear regression analysis was used. Results: The mean age of subjects was 20.21±2.21 years and there wasn't a significant difference in the age of sex groups (P=0.211). There was a significant difference in the height of cases between two sex groups (P=0.0001). In addition, there was a significant difference in the FAL of sex groups (P=0.0001). In addition, there was a correlation between height and FAL of cases (r=0.801, P=0.0001). There was a correlation between height and FAL of male cases (r=0.668, P=0.002) and female cases (r=0.6, P=0.0001). Conclusion: According to the results, FAL was a suitable factor for height estimation. In addition, this factor is a moderate predictor of height in native males and females of Kerman.